Louis Vuitton, Gucci, and Audi: The Luxury Retail Sector in India - Will it Grow or Go? - Bothra, Neha (Indian Journal of Marketing, 2014)
In an era where competitive companies, big brands, and intellectual industrialists fail to sustain, one lucrative market has managed not only to survive, but also to entice a variety of eyeballs towards it with every passing day. The Indian luxury market has evolved and is expected to attain a value of $15 billion by 2015. Privatization, industrial and technological revolution have catalyzed economic growth rates and widespread prosperity. Studying the consumer behaviour of these quality conscious and price insensitive consumers is entirely different from the rest. Although the luxury market exists in Delhi, Mumbai, and Bangalore, it is now moving towards tier two towns as well. The luxury market is a rising market because it is easy to get addicted to, but difficult to do without. This study uses secondary data to analyze contemporary retailing in India for the luxury market and explains how the luxury retail market is yet to achieve its boom. The paper also analyzes the developments in multi-dimensional luxury and lifestyle retailing in India and discusses the prospects and challenges for luxury retailers in India.